STRATEGI PENINGKATAN KOMPETENSI PEKERJA PARIWISATA – STUDI KASUS SERTIFIKASI BNSP DI BINTAN - Tyas Rosani (Jurnal Inovasi Penelitian, 2022)
Competency Certification is a demand as well as a need in facing job competition. In accordance with Indonesia Regulation, PP No 52 year 2012 concerning professional certification and tourism business certification, the certificate for the worker is a written evidence or a formal evidence of their work ability or their competency. The Certification Program is a government program through the BNSP which is provided by Professional Certification Institute (LSP). This research is analyzed that the certification of competency is one of Human Resources strategy to develop the workforce. This research using a descriptive qualitative approach, data source obtained from field observation, interview and documentation. Certification for tourism workforce is very important and essential. Refer to the result, finding that certification program has been created by the government should be utilized maximally either by assessors in tourism or tourism human resources in Bintan also by the local stakeholder. Developing tourism worker’s skill and competency is depending on support from local government, stake holder and from the company.